Separation of Highly Pure Semiconducting Single-Wall Carbon Nanotubes in Alkane Solvents via Double Liquid-Phase Extraction - Ahmad Al Shboul; Mohamed Siaj; Jerome Claverie (Nanomaterials)
This study delves into the distinctive selective property exhibited by a non-conjugated cholesterol-based polymer, poly(CEM11-b-EHA7), in sorting semiconducting single-walled carbon nanotubes (s-SWCNTs) within isooctane. Comprised of 11 repeating units of cholesteryloxycarbonyl-2-hydroxy methacrylate (CEM) and 7 repeating units of 2-ethylhexyl acrylate (EHA), this non-conjugated polymer demonstrates robust supramolecular interactions across the sp2 surface structure of carbon nanotubes and graphene. When coupled with the Double Liquid-Phase Extraction (DLPE) technology, the polymer effectively segregates s-SWCNTs into the isooctane phase (nonpolar) while excluding metallic SWCNTs (m-SWCNTs) in the water phase (polar). DLPE proves particularly efficient in partitioning larger-diameter s-SWCNTs (0.85–1.0 nm) compared to those dispersed directly in isooctane by poly(CEM11-b-EHA7) using direct liquid-phase exfoliation (LPE) techniques for diameters ranging from 0.75 to 0.95 nm. The DLPE method, bolstered by poly(CEM11-b-EHA7), successfully eliminates impurities from s-SWCNT extraction, including residual metallic catalysts and carbonaceous substances, which constitute up to 20% of raw HiPCO SWCNTs. DLPE emerges as a scalable and straightforward approach for selectively extracting s-SWCNTs in nonpolar, low-boiling-point solvents like alkanes. These dispersions hold promise for fabricating fast-drying s-SWCNT inks, which are ideal for printed and flexible thin-film transistors.